How Do Different Product Categories Involve the Retailer’s Assortment Management Strategies? The Case of the US - José Luis Ruiz-Real; Juan Uribe-Toril; María del Mar Martín-García (Amfiteatru Economic)
The effectiveness of specific marketing actions taken by retailers is different depending on the product category. This paper aims to analyse the role that different product categories play in consumer response to retail assortment. Hypotheses are tested in an online experiment using consumers belonging to a large panel in the US Both assortment size and composition were manipulated. Four product categories were considered. The results show the need for retailers to offer different strategies based on the role that categories play in consumer response to retail assortment.